ANALYSIS OF GRAIN SIZE AND MINERALOGY OF HEAVY MINERAL GRAINS IN PALANGKA RAYA AREA, CENTRAL KALIMANTAN PROVINCE - Nurzakiyah, Halimah; Rosana, Mega Fatimah; Sunarie, Cecep Yandri; Ernowo, Ernowo (Faculty of Geological Engineering, Universitas Padjadjaran, 2025)
The Palangka Raya area is situated on the island of Borneo, specifically within the Central Kalimantan province. The study area is composed of a lithological sequence comprising fine-coarse quartz sandstone and cross-layered conglomerate, with components in the form of malleable and granitic rocks from the Dahor Formation (TQd) and alluvium deposits. This sequence has the potential for heavy mineral deposits associated with sedimentary sands. This study aimed to calculate and identify grain size and heavy mineral content distribution within the investigated area. The research was conducted using a combination of grain size analysis and grain mineralogy analysis on six mesh numbers. The results of the grain size analysis indicate that the majority of samples exhibit grain sizes within the mesh numbers -10+18 and -60+140. The results of the grain mineralogy analysis revealed the presence of heavy minerals, including cassiterite, hematite, biotite, chalcopyrite, zircon, rutile, ilmenite, garnet, amphibole, and staurolite. Heavy mineral variations were observed on mesh numbers -60+140 and <140. These minerals are believed to have originated from metamorphic rocks, S-type granitic rocks, and I-type granitic rocks.